RESISTANCE OF ATMOSPHERIC AND COLD CELLULAR CONCRETE - Jalolov Zayniddin; Sodiqjon Khakimov Namangan (Journal of Geography, Regional Planning and Development, 2024)
The article focused on the literature of scientists who worked on the resistance of cellular concrete to cold and atmospheric conditions